Armored Men-At-Arms in the Battle of Orsha (1514). Arms, Armor and Tactics - Hutsul, Volodymyr (Narzędzia wojny, 2023)
The article is devoted to the arms, armor and tactics of its use by the Jagiellonian men-at arms in the Battle of Orsha (1514). To solve the problem, visual and textual sources of the time were used, among the latter, not only narrative, but also fencing treatises of the first half of the 16th century, which highlight the peculiarities of the use of knightly weapons in horse combat, were considered. As a result of source analysis, the author came to the conclusion that the armored cavalry of the Jagiellonian army did not fundamentally differ from the Western European chivalry of the time either in terms of equipment or combat techniques. Comparing the iconography of knightly weapons in the main visual source related to the battle -– the „Battle of Orsha” panel from the National Museum in Warsaw with clearly dated examples of the period of the first decade -– the middle of the second decade of the 16th century. we can say with certainty that the panel does not contain anachronisms depicted.